Development of calcium silicate-coated expanded clay based form-stable phase change materials for enhancing thermal and mechanical properties of cement-based composite. (1st November 2018) - Liu, Yushi; Xie, Mingjun; Xu, Entao; Gao, Xiaojian; Yang, Yingzi; Deng, Hongwei
Highlights: A novel calcium silicate-coated expanded clay is prepared as one stable form of PCM. Good thermal stability of CS-ECPCM is presented by cladding calcium silicate on expanded clay. Interfacial zone between CS-ECPCM and cement is enhanced by secondary encapsulation. CS-ECPCM used as TESCMs exhibit acceptable strength and excellent thermal performance. Abstract: In this study, the thermal energy storage cement mortar (TESCM) was developed by incorporating calcium silicate-coated paraffin/expanded clay based form-stable PCMs (CS-ECPCM). The thermophysical properties, microstructure and spectroscopic characterization of CS-ECPCM and the thermal and mechanical properties of the TESCM were investigated. MIP and SEM results show that the paraffin mixture consisted of 52# paraffin and liquid paraffin can be well impregnated into expanded clay (EC) pores. The thermal-cycling test results indicate the good thermal stability of CS-ECPCM by the cladding of three-layer calcium silicate. And DSC results reveal that the CS-ECPCM has the phase change temperature and latent heat of 23.67 °C and 24.43 J/g, respectively, and the lower phase change temperature of CS-ECPCM compared with pure paraffin mixture can be supported by FT-IR and Raman spectra results. Furthermore, the CS-ECPCM was incorporated in cement mortar at 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100%, by weight of sand. However, the interfacial zone structures between CS-ECPCM and cement has been enhanced by secondary encapsulation of calcium silicate, relieving the decrease in the compressive strength of TESCM. In addition, the thermal conductivities of the TESCMs decrease with the increase of mixing amount of CS-ECPCM, which are positive to their thermal insulation performance. And the excellent thermal energy storage performance of TESCMs is clearly suggested by the results of specific heat capacity test and heating test.